(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Result of artistic studies and experiments in dialogue with the Performing Arts course at Federal University of Grande Dourados, this reflection addresses sociocultural issues in the problematization of socio-discursive imaginaries that surround the hybrid theatrical-musical universe. Through the popular musical theater of So and so, which premiered at the Municipal Theater of Dourados in 2018, we observe concerns that pervade tensions between popular culture and high culture, and that can act as an encouragement in the propagation of stereotypes. The topics of the article go through the recognition of these tensions, through the dialogue with the work So and so, and culminates in reverberations in the academic sphere with proposals for discussions in teaching and research spaces.